2014
DOI: 10.5751/es-06300-190209
|View full text |Cite
|
Sign up to set email alerts
|

Information Networks and Power: Confronting the "Wicked Problem" of REDD+ in Indonesia

Abstract: ABSTRACT. Reducing Emissions from Deforestation and Forest Degradation (REDD+) is a priority issue for forest and climate policy in Indonesia, and REDD+ policy-making activity has been characterized by considerable public consultation. Despite this engagement, discussions on REDD+ in Indonesia are reported to have remained top-down, a disconcerting pattern when adaptive governance and transformational change require cross-scale and cross-sectoral communication. Explicitly modeling the patterns of information e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 62 publications
1
32
0
1
Order By: Relevance
“…For example, analysis of information sharing in the current REDDþ process in Indonesia found a disconnect between governmental, transnational and domestic civil society organizations [14]. This suggests that multiple perspectives are unlikely to be fully integrated, and that groups may regard one another as information sources lacking in credibility and legitimacy.…”
Section: Introductionmentioning
confidence: 99%
“…For example, analysis of information sharing in the current REDDþ process in Indonesia found a disconnect between governmental, transnational and domestic civil society organizations [14]. This suggests that multiple perspectives are unlikely to be fully integrated, and that groups may regard one another as information sources lacking in credibility and legitimacy.…”
Section: Introductionmentioning
confidence: 99%
“…Such analysis underpins the papers in this special feature that investigate homophily in policy coalitions (Moeliono et al 2014, Rantala andDi Gregorio 2014).…”
Section: Network Analysismentioning
confidence: 99%
“…In the absence of obvious short-term win-win outcomes for all, at the national level such tensions emerge especially during policy negotiations about the details of the national REDD+ strategies Angelsen 2012, Brockhaus andDi Gregorio 2014). To understand what hinders or enables the transformational change required for realizing effective, efficient, and equitable REDD+ strategies it is important that we understand the processes that underlie such challenges.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the role of government agencies was still uncertain. This lack of coordination was confirmed in studies of Moeliono et al (2014) and Gallemore et al (2014), and will likely lead to inefficiencies when implemented. To overcome these issues, we suggest a strong coordinating body needs to be established that can reduce institutional fragmentation while simplifying the organisational structure of REDD.…”
Section: Towards An Integrated Safeguard Approachmentioning
confidence: 88%
“…Also, several studies have revealed a lack of coordination within the multi-scalar policy setting of REDD+ (Atela et al, 2015;Gallemore et al, 2014;Moeliono et al, 2014).…”
Section: Multi-scalar Challenges and Complexitiesmentioning
confidence: 99%